(w-11)(w-4)=-10

Simple and best practice solution for (w-11)(w-4)=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (w-11)(w-4)=-10 equation:


Simplifying
(w + -11)(w + -4) = -10

Reorder the terms:
(-11 + w)(w + -4) = -10

Reorder the terms:
(-11 + w)(-4 + w) = -10

Multiply (-11 + w) * (-4 + w)
(-11(-4 + w) + w(-4 + w)) = -10
((-4 * -11 + w * -11) + w(-4 + w)) = -10
((44 + -11w) + w(-4 + w)) = -10
(44 + -11w + (-4 * w + w * w)) = -10
(44 + -11w + (-4w + w2)) = -10

Combine like terms: -11w + -4w = -15w
(44 + -15w + w2) = -10

Solving
44 + -15w + w2 = -10

Solving for variable 'w'.

Reorder the terms:
44 + 10 + -15w + w2 = -10 + 10

Combine like terms: 44 + 10 = 54
54 + -15w + w2 = -10 + 10

Combine like terms: -10 + 10 = 0
54 + -15w + w2 = 0

Factor a trinomial.
(6 + -1w)(9 + -1w) = 0

Subproblem 1

Set the factor '(6 + -1w)' equal to zero and attempt to solve: Simplifying 6 + -1w = 0 Solving 6 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1w = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1w = 0 + -6 -1w = 0 + -6 Combine like terms: 0 + -6 = -6 -1w = -6 Divide each side by '-1'. w = 6 Simplifying w = 6

Subproblem 2

Set the factor '(9 + -1w)' equal to zero and attempt to solve: Simplifying 9 + -1w = 0 Solving 9 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1w = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1w = 0 + -9 -1w = 0 + -9 Combine like terms: 0 + -9 = -9 -1w = -9 Divide each side by '-1'. w = 9 Simplifying w = 9

Solution

w = {6, 9}

See similar equations:

| 7a=2(a-20)+30 | | X^2-72x+1152=0 | | 0,5x+3=-10,5 | | 10x+28=6x+72 | | 171-3x=42x+16 | | 1,2x+3=-11,2 | | 6+2i/9-3i | | -9/4d+1=4/d+1 | | -8-4x=-7-9x | | 1/12d-4/3d=15 | | 1/12d-4/3d | | 1/12d-4/3d=y | | X^2-64x+962=0 | | 5y/6-2y/3+5=y | | X^2-64x-962=0 | | 7m^2+9m+5=0 | | -37(14x)+28(21x)=72-72+-166+96 | | (7+2i)/(3-3i) | | 4(x-4)+2x-3=4(4-x) | | 3n^2=-10n-4 | | 16y-5+2y=70 | | ((6x+18)/(5x^2))/((6x^3)/(25)) | | X^2-60x+960=0 | | x^2+15x=450 | | x^2+11x=350 | | 6x^3-29x^2+4x-45=0 | | 6(1-x)-2(x-2)=2-4(x-4) | | x^2+11=350 | | (1/5)(45-X) | | (2x+5)/(7x+22) | | 12x+15y=1000 | | 9-21=y-2+16 |

Equations solver categories